Analisis Implementasi Pengukuran Suhu Tubuh Manusia dalam Pandemi Covid-19 di Indonesia - Unang Achlison (STEKOM PRESS, 2020)
The corona virus (Covid-19) has attacked almost the entire world, including Indonesia. Places where community activities must comply with health protocols, one of which is checking human body temperature. The measurement of human body sensors is a very significant difference even though it is applied to the same human body, this is due to several factors. This research analyzes the measurement results of the human body temperature sensor. This study aims to determine an effective and efficient human body temperature sensor. The process of measuring human body temperature uses a microcontroller-based temperature sensor. After the results of temperature measurements using different temperature sensors are obtained, the measurement results are analyzed and compared to obtain an effective and efficient temperature sensor. Based on the analysis, the results of measuring human body temperature using a thermal camera are an effective and efficient sensor.